2023
DOI: 10.5530/pj.2023.15.34
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin from Curcuma longa L. as Dual Inhibitors Against Indonesian SARS-CoV-2 Isolates: A Molecular Docking Study

Abstract: Using Lipinski's rule of five on the SCFBIO web server (http://www.scfbio-iitd. res.in/software/ drugdesign/lipinski.jsp), curcumin was utilized for further drug-likeness analysis. It was regarded as a successful forecast when two minimal guidelines ABSTRACT COVID-19 has become a global pandemic since 2020. The search for promising drugs based on the abundant herbal ingredients in Indonesia is one of the breakthroughs. Curcumin is a chemical compound with various potentials such as antioxidant, anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Concerning other plants, several molecular docking and in vitro studies showed the probable anti-SARS-CoV-2 effect of their compounds. Some compounds can act by inhibition of SARS-CoV-2 M pro , such as S-Allylcysteine sulfoxide (Alliin), diallyl trisulfide, diallyl disulfide, and diallyl sulfide of Allium sativum (Pandey et al 2021), quercetin, oleanolic acid, and cyanidin of Allium cepa (Fitriani et al 2020, Bondhon et al 2021, zingiberenol, zingiberol, and 6-gingerol of Zingiber officinale (Rathinavel et al 2020, Rabie 2022, eucalyptol (1,8 cineole) of Eucalyptus globulus (Sharma 2020, Torres Neto et al 2022, Apigenine-7-glucoside and oleuropein of Olea europaea (Khaerunnisa et al 2020), nigellidine and α-hederin of Nigella sativa (Bouchentouf & Missoum 2020), tangshenoside III, rutin, and hesperidin of Saussurea costus (Houchi & Messasma 2022), and curcumin of Curcuma longa (Nidom et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning other plants, several molecular docking and in vitro studies showed the probable anti-SARS-CoV-2 effect of their compounds. Some compounds can act by inhibition of SARS-CoV-2 M pro , such as S-Allylcysteine sulfoxide (Alliin), diallyl trisulfide, diallyl disulfide, and diallyl sulfide of Allium sativum (Pandey et al 2021), quercetin, oleanolic acid, and cyanidin of Allium cepa (Fitriani et al 2020, Bondhon et al 2021, zingiberenol, zingiberol, and 6-gingerol of Zingiber officinale (Rathinavel et al 2020, Rabie 2022, eucalyptol (1,8 cineole) of Eucalyptus globulus (Sharma 2020, Torres Neto et al 2022, Apigenine-7-glucoside and oleuropein of Olea europaea (Khaerunnisa et al 2020), nigellidine and α-hederin of Nigella sativa (Bouchentouf & Missoum 2020), tangshenoside III, rutin, and hesperidin of Saussurea costus (Houchi & Messasma 2022), and curcumin of Curcuma longa (Nidom et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Drug-likeness analysis results must be no violation and ≥0.50 as well as high score for pharmacokinetics. 22 Positive predictions are distinguished to fulfill the criteria of each category with check mark (√) and will be continued to the next step. 21…”
Section: Drug-likeness Analysismentioning
confidence: 99%
“…The combination of Moringa oleifera Lam. and C. longa is predicted to have antiviral and anti-inflammatory activity through a dual inhibitory mechanism involving cryptochlorogenic acid and curcumin [13][14][15][16]. One study reported that curcumin may mitigate damage to the intestinal barrier by inhibiting inflammatory responses and attenuating stress injury [17].…”
Section: Introductionmentioning
confidence: 99%